Analysis Of Diagnostic System For Alzheimer’s Disease - Nancy, A; Vijaykumar, S (International Journal of Computer Sciences and Engineering, 2025)
Alzheimer’s disease was the leading cause of death. There is no cure and no effective treatment for Alzheimer’s disease. The challenges will increase in intensity as demographic changes, particularly the aging of baby boomers, take hold. High prediction of Alzheimer’s, developed in therapy, and appropriate care modalities that likely observe significant investment. The Alzheimer’s disease Neuro Imaging Initiative (ADNI) is an ongoing, longitudinal study designed to develop clinical, imaging, genetic, and biochemical biomarkers for the early detection and tracking of Alzheimer’s disease (AD). The required accomplishments of ADNI have been as follows: the development of standardized methods for clinical tests, magnetic resonance imaging (MRI), positron emission tomography (PET), and cerebrospinal fluid (CSF).In the recent system, a large number of people are suffering from brain related diseases. Studying and finding the solutions for those diseases is the requirement of our need. Dementia is one such disease of the brain. This is most reason for the loss of cognitive functions such as reasoning, memory and other mental abilities which may be due to trauma or normal ageing. Alzheimer’s disease is one of the most dangerous mental disorders which accounts to 60-80% of mental disorders. Diagnosis of this disease at an early stage will help the patients to lead a quality life for the remaining tenure of their life. The focus of the work is to have a review on different neuro psychological tests, the various algorithms used for the purpose of diagnosis, and the tool that may be used for the analysis